Breath figures decorated silica-based ceramic surfaces with tunable geometry from UV cross-linkable polysiloxane precursor. Issue 4 (April 2018) - Carlomagno, Cristiano; Speranza, Giorgio; Aswath, Pranesh; Sorarù, Gian Domenico; Migliaresi, Claudio; Maniglio, Devid
Abstract: Little has been published so far on the fabrication of porous ceramic films by using the Breath Figure method. In this work we explored the Breath Figure method to obtain ceramics with patterned surfaces. A UV cross-linkable polysiloxane was used to produce Breath Figures with tunable pore size. Pores formation, in terms of size and distribution on the polysiloxane films, were studied as a function of the concentration of the starting solution and time before UV irradiation. The polymeric breath figures were then pyrolyzed in controlled atmosphere to obtain, through the polymer-derived ceramic, PDCs, route the corresponding ceramic preserving the original porous surface. Pyrolysis under different gases, in particular air, nitrogen and ammonia, allows obtaining films of three different ceramic materials: silicon dioxide, SiO2, silicon oxycarbide, SiOC and silicon oxynitride, SiON respectively.